Neural Correlates of Autobiographical Memory in PTSD - Qureshi, Aamna (My University, 2019)
This thesis examines the neural correlates of autobiographical memory retrieval among individuals with military-related PTSD, a population with increased illness burden and decreased treatment response. Although cognitive deficits, including in autobiographical recall, have been identified in PTSD, the mechanisms underlying these deficits remains unclear. Here, a series of studies have pointed towards alterations in the neural pathways underlying autobiographical recall in PTSD. Despite these observations, it remains unclear how key clinical variables, such as dissociation and early life trauma, might impact patterns of neural response during autobiographical recall in PTSD. The original work presented in this thesis examines emotional and traumatic memory retrieval in a sample of patients with military-related PTSD, trauma-exposed participants, and healthy controls and includes analysis of the relation between patterns of neural activation during autobiographical memory retrieval and key clinical variables associated previously with disease-related alterations in cognitive functioning. Our findings of increased lingual activity point towards aberrant implicitly cued memory function in military members and veterans with PTSD during traumatic memory retrieval. In addition, activation in the frontal operculum suggests that trauma-exposed military members and veterans without PTSD showed increased engagement of emotion regulatory strategies during retrieval of negative memories. Finally, we found an association between dissociative symptoms and activation observed in frontal and posterior regions during trauma memory retrieval in trauma-exposed military members and veterans. In addition to increasing core scientific knowledge surrounding the neural correlates of autobiographical memory recall in trauma-exposed military members with and without PTSD, our results highlight the urgent need to characterize further the role of dissociative symptoms in cognitive dysfunction among individuals with PTSD.